Collaborating for smarter mosques - Noradzan, Haslinda; Wan Ghani, Wan Aryati; Sa’dan, Siti ‘Aisyah; Md Sarif, Shamsudin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
A smart mosque (masjid pintar) integrates modern technologies, digital systems, and sustainable design to improve mosque functions and strengthen community connections. Through automation and smart features, it optimizes energy and water use, enhances security, and improves comfort with better ventilation, lighting, and sound systems. These technologies also support accessibility for the elderly and people with disabilities, manage overcrowding during peak times, and enable predictive maintenance to reduce repair costs. This approach highlights how community-driven innovation, together with university experts, contributes to developing smarter and more efficient mosque facilities.